Environment-like exposure of free-living stages of Haemonchus contortus to albendazole: The intra- and intergeneration stability of altered expression of UDP-glycosyl transferases and ABC-transporters - Štěrbová, Karolína; Thuy, Linh Nguyen; Žofka, Martin; Matoušková, Petra; Krátký, Josef; Skálová, Lenka (Chemosphere, 2025)
Anthelmintic drugs are widespread environmental contaminants, but their impact is still poorly understood. Although contact of parasitic nematode Haemonchus contortus with traces of anthelmintic drug albendazole (ABZ) altered the expression and activity of several UDP-glycosyl transferases (UGTs) and P-glycoproteins (Pgps, belonging to ABC-transporters), key enzymes in endogenous and xenobiotic metabolism, it is not known whether these changes will last during the life cycle and pass to the next generations. In the present study simulating the environmental-like exposure, free-living stages of H. contortus were exposed or unexposed to a sub-lethal dose of ABZ and its transformation products (ABZs) during L3 development. The L3 served for lambs' infection and obtaining of H. contortus adults and eggs, which were again exposed or unexposed to ABZs during L3 development. The expression pattern of UGTs and Pgps was analysed and compared in the first generation of L3, in the adults, and in the second generation of L3. The results showed that ABZs exposition during larvae development altered the expression of several ugt and pgp genes in L3 and adults. The intrageneration stability of ABZs-evoked changes was observed in the case of three genes, four genes maintained the intergeneration stability. Interestingly, ABZs-induced changes in the expression of some genes became apparent only in the second generation of L3. Taking together, contact of free-living stages of H. contortus with traces of ABZs in the environment evokes changes in the expression of certain UGTs and Pgps, with some of these changes being intra- and inter-generation stable.
Keywords: Haemonchus; Animals; ovce; ATP-Binding Cassette Transporters; stadia vývoje; ABC transportéry; zvířata; Anthelmintics; Life Cycle Stages; Sheep; Albendazole; albendazol; anthelmintika; Glycosyltransferases; glykosyltransferasy